Profitability, Liquidity, and Leverage: Exploring Financial Distress in the Mining Sector: Dampak Profitabilitas, Likuiditas, dan Leverage terhadap Kesulitan Keuangan pada Perusahaan Sektor Pertambangan - Rosita Umamah; Nurasik Nurasik (Universitas Muhammadiyah Sidoarjo, 2023)
In the era of the Industrial Revolution 4.0, the competitive landscape among companies is intensifying, necessitating effective business strategies to avoid bankruptcy. This research examines the impact of profitability, liquidity, and leverage on financial distress in mining sector companies listed on the IDX from 2018 to 2020. Using a quantitative approach, the study analyzes data from a population of 41 mining sector companies. The findings reveal that profitability and liquidity, measured through ratios, do not significantly affect financial distress. However, leverage has a significant influence on financial distress. These results provide valuable insights for mining companies in formulating business strategies and managing financial risk to mitigate the potential for distress. The research contributes to the literature on financial distress in the context of the mining sector, addressing the challenges of increased competition and the need for sustainable company performance. Highlights: Determinants of financial distress: Investigating the impact of profitability, liquidity, and leverage on the occurrence of financial distress in mining sector companies. Empirical analysis: Analyzing the relationship between these variables and financial distress using quantitative research methods and ratios. Implications for mining sector companies: Providing insights for companies in the mining sector to better manage their profitability, liquidity, and leverage in order to mitigate the risk of financial distress and maintain sustainable performance. Keywords: profitability, liquidity, leverage, financial distress, mining sector